Accounting principles for lawyers - Holgate, Peter (Cambridge University Press, 2006)
This book explains those aspects of accounting that lawyers need to understand, such as how accounting in the UK interacts with companies legislation, and the move to international accounting standards. For the general practitioner as well as lawyers working in corporate and commercial law and tax.